Mechanoactivation of the angiotensin II type 1 receptor induces β‐arrestin‐biased signaling through Gαi coupling. Issue 4 (4th January 2018) - Wang, Jialu; Hanada, Kenji; Gareri, Clarice; Rockman, Howard A.
Abstract: Ligand activation of the angiotensin II type 1 receptor (AT1R), a member of the G protein‐coupled receptor (GPCR) family, stimulates intracellular signaling to mediate a variety of physiological responses. The AT1R is also known to be a mechanical sensor. When activated by mechanical stretch, the AT1R can signal via the multifunctional adaptor protein β‐arrestin, rather than through classical heterotrimeric G protein pathways. To date, the AT1R conformation induced by membrane stretch in the absence of ligand was thought to be the same as that induced by β‐arrestin‐biased agonists, which selectively engage β‐arrestin thereby preventing G protein coupling. Here, we show that in contrast to the β‐arrestin‐biased agonists TRV120023 and TRV120026, membrane stretch uniquely promotes the coupling of the inhibitory G protein (Gαi ) to the AT1R to transduce signaling. Stretch‐triggered AT1R‐Gαi coupling is required for the recruitment of β‐arrestin2 and activation of downstream signaling pathways, such as EGFR transactivation and ERK phosphorylation. Our findings demonstrate additional complexity in the mechanism of receptor bias in which the recruitment of Gαi is required for allosteric mechanoactivation of the AT1R‐induced β‐arrestin‐biased signaling. Abstract : In this study, we identify a new molecular mechanism for β‐arrestin‐biased AT1R signaling, and demonstrate the mechanistic divergence of signaling triggered by the different modes of receptor activation. Membrane stretch, which has been shown to activate β‐arrestin‐biased AT1R signaling without activating Gαq, specifically promotes the recruitment of another subtype of G proteins, Gαi, to the AT1R to mediate subsequent β‐arrestin‐dependent signaling. In contrast, the Gαi recruitment and the dependence of Gαi for β‐arrestin‐mediated signaling was not observed for the balanced agonist AngII, or, remarkably, the β‐arrestin‐biased agonists TRV120023 and TRV120026.